Southeast Asian cartoon art : history, trends and problems - Lent, John A. (McFarland & Company, Inc., Publishers, 2014)
"This is the first overview of cartoon art in this important cultural nexus of Asia. The eight chapters provide historical and present-day overviews of cartoons and comics in Indonesia, the Philippines, Thailand, Cambodia, and Vietnam, and sociocultural and political analyses of cartooning in Singapore, Myanmar, and Malaysia"--